Harnessing exosomes and plant-derived exosomes as nanocarriers for the efficient delivery of plant bioactives - Kathait P.; Patel P.K.; Sahu A.N. (My University, 2025)
Exosomes, a category of extracellular vesicle (EV), are phospholipid bilayer structures ranging from 30 to 150 nm, produced by various organisms through the endosomal pathway. Recent studies have established the utilization of exosomes as nanocarriers for drug distribution across various therapeutic areas including cancer, acute liver injury, neuroprotection, oxidative stress, inflammation, etc. The importance of plant-derived exosomes and exosome vesicles derived from mammalian cells or milk, loaded with potent plant bioactives for various therapeutic indications are discussed along with insights into future perspectives. Moreover, this review provides a detailed understanding of exosome biogenesis, their composition, classification, stability of different types of exosomes, and different routes of administration along with the standard techniques used for isolating, purifying, and characterizing exosomes. © 2024 Informa UK Limited, trading as Taylor & Francis Group.